Ecogames: Playful Perspectives on the Climate Crisis, edited by Laura op de Beke, Joost Raessens, Stefan Werning and Gerald Farca (Amsterdam University Press, 2024) - Lykke Guanio-Uluru (Eludamos)
A review of the voluminous anthology Laura op de Beke, Joost Raessens, Stefan Werning and Gerald Farca (eds.): Ecogames: Playful Perspectives on the Climate Crisis. Published by Amsterdam University Press in their Green Media series, 2024. ISBN: 978-9-463-72119-6, 612 pages.